2017
DOI: 10.1016/j.ymgmr.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Role of AMPD2 in impaired glucose tolerance induced by high fructose diet

Abstract: A high intake of products containing fructose is known to mediate insulin resistance. In the liver, AMPD2, an isoform of AMPD, has important glucose metabolic homeostasis functions including maintenance of AMP-activated protein kinase (AMPK). We speculated that AMPD2 induces impaired glucose tolerance in individuals who consume a high-fructose diet. We gave either a normal-chow (NCD) or high-fructose (HFrD) diet for 40 days to 8-week-old male wild-type (WT) and Ampd2 −/− homozygote (A2 −/−) C57BL/6 mice. A glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Adenosine monophosphate deaminase 2 ( Ampd2 , Table 3 ), an enzyme that converts AMP to inosine monophosphate (IMP) and maintains cellular guanine nucleotide pools [ 43 ], was downregulated, potentially attenuating protein synthesis. This protein also mediates gluconeogenesis in the rodent liver [ 44 ] and, together with Pde4d upregulation ( Table 3 ), suggests pathways impacting cellular quiescence may be altered by spaceflight.…”
Section: Resultsmentioning
confidence: 99%
“…Adenosine monophosphate deaminase 2 ( Ampd2 , Table 3 ), an enzyme that converts AMP to inosine monophosphate (IMP) and maintains cellular guanine nucleotide pools [ 43 ], was downregulated, potentially attenuating protein synthesis. This protein also mediates gluconeogenesis in the rodent liver [ 44 ] and, together with Pde4d upregulation ( Table 3 ), suggests pathways impacting cellular quiescence may be altered by spaceflight.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been reported that AMPD2 knock‐out mice are protected from the glycaemic dysregulation caused by a high fructose diet. An accumulation of AMP would be expected in these mice, but, apparently, the protection exerted by enzyme ablation was not mediated by AMPK activation . Finally, Lanaspa et al .…”
Section: Enzymes Participating In Adenylate Metabolismmentioning
confidence: 92%
“…Indeed, it has been reported that AMPD2 knock-out mice are protected from the glycaemic dysregulation caused by a high fructose diet. An accumulation of AMP would be expected in these mice, but, apparently, the protection exerted by enzyme ablation was not mediated by AMPK activation [75]. Finally, Lanaspa et al [76] demonstrated that a decrease in AMPD2 activity in hibernating ground squirrel during the winter determines the switch of the metabolic arrangement of the liver from lipogenic during the summer to fat oxidizing during hibernation.…”
Section: Amp Deaminasementioning
confidence: 96%
“…The relation between insulin resistance, fasting hyperglycemia and glucose intolerance has been said to be mediated by increased synthesis of nonesterified fatty acid (NEFA) and subsequently triacylglycerol (triglyceride) production in the liver from fructose metabolism 44 . Ectopic lipid deposition in liver and skeletal muscles and consequently intramyocellular lipid accumulation result in the production of toxic lipid-derived metabolites which cause serine/threonine phosphorylation of insulin substrate, and this has been shown to reduce insulin signaling, 45,46 thus causing insulin resistance. The insulin resistance and obesity induced by fructose feeding in experimental animals induce compensatory hyperinsulinemia 47 which may cause beta cell exhaustion, thus impairing beta cell function.…”
Section: Fig 10: Metformin Response Test Of Fructosementioning
confidence: 99%